Ownership Structure and Export Performance: Firm-Level Evidence from the Republic of Korea - Sangho Kim; Donghyun Park (Asian Development Bank (ADB), 2011)
The central objective of our paper is to empirically examine the relationship between the ownership structure of firms and their export performance. To do so, we use data from the Republic of Korea, a classic example of successful export-oriented industrialization. While a large and growing empirical literature investigates the relationship between the ownership structure and overall performance of firms, there are almost no studies that delve into the issue of whether the concentration of ownership has a positive or negative effect on export performance. The primary contribution of our study is to help remedy this serious gap in the empirical literature on ownership and performance. Our empirical results indicate that Korean firms with more concentrated ownership are more likely to be exporters, and to export more.
hdl:11540/1990
Keywords: 330; Export; Eigentümerstruktur; Industrie; Südkorea